Correlation of microglial activation with white matter changes in dementia with Lewy bodies - Nicastro, Nicolas (Neuroimage Clin, 2020)
Dementia with Lewy bodies (DLB) is characterized by alpha-synuclein protein deposition with variable degree of concurrent Alzheimer's pathology. Neuroinflammation is also increasingly recognized as a significant contributor to degeneration. We aimed to examine the relationship between microglial activation as measured with [(11)C]-PK11195 brain PET, MR diffusion tensor imaging (DTI) and grey matter atrophy in DLB. Nineteen clinically probable DLB and 20 similarly aged controls underwent 3T structural MRI (T1-weighted) and diffusion-weighted imaging. Eighteen DLB subjects also underwent [(11)C]-PK11195 PET imaging and 15 had [(11)C]-Pittsburgh compound B amyloid PET, resulting in 9/15 being amyloid-positive. We used Computational Anatomy Toolbox (CAT12) for volume-based morphometry (VBM) and Tract-Based Spatial Statistics (TBSS) for DTI to assess group comparisons between DLB and controls and to identify associations of [(11)C]-PK11195 binding with grey/white matter changes and cognitive score in DLB patients. VBM analyses showed that DLB had extensive reduction of grey matter volume in superior frontal, temporal, parietal and occipital cortices (family-wise error (FWE)-corrected p < 0.05). TBSS showed widespread changes in DLB for all DTI parameters (reduced fractional anisotropy, increased diffusivity), involving the corpus callosum, corona radiata and superior longitudinal fasciculus (FWE-corrected p < 0.05). Higher [(11)C]-PK11195 binding in parietal cortices correlated with widespread lower mean and radial diffusivity in DLB patients (FWE-corrected p < 0.05). Furthermore, preserved cognition in DLB (higher Addenbrookes Cognitive Evaluation revised score) also correlated with higher [(11)C]-PK11195 binding in frontal, temporal, and occipital lobes. However, microglial activation was not significantly associated with grey matter changes. Our study suggests that increased microglial activation is associated with a relative preservation of white matter and cognition in DLB, positioning neuroinflammation as a potential early marker of DLB etio-pathogenesis.